PERANCANGAN JALAN LAYANG TUGU KEBON JERUK - Fitria Arfan, Irfani
The Tugu Kebon Jeruk Intersection is located at the intersection between Jalan Panjang and Jalan Lapangan Bola, West Jakarta. The design process of the flyover was started by creating an initial design based on bridge specifications and existing conditions, and then continued by structural analysis using SAP2000 applications. These analysis results are then used to design upper structural components that include PCI girders, made from pre-tensioned concrete material, as well as pier, pierhead, and plate that are made of reinforced concrete material. The design process continued by calculating the pre-tensioning force working on the girder, analyzing the tension that occur during the construction phases, analyzing the deflection that take place on the girder, and designing the layout of the tendon. The pier and piehead components are designed to be earthquake resistant, and the designed feature include longitudinal reinforcement, shear reinforcement, and torsion reinforcement. In the pier component, a P-? is checked to to determine if the lateral displacement that occur in the pier, both in the lateral and longitudinal directions, meets the applicable requirements.